2016
DOI: 10.1007/s11154-016-9366-z
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa/Acne inversa: an endocrine skin disorder?

Abstract: Hidradenitis suppurativa / acne inversa (HS) is a chronic inflammatory, debilitating skin disorder with a largely unknown etiology. However, many observations such as the typical onset of the disease after puberty, the female predominance, the pre-menstrual flare ups and the improvement during pregnancy suggest a contribution of endocrinological factors to the emergence of the disease. In addition, the reported efficacy of anti-androgen treatment on HS indicates a possible involvement of androgens in the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 76 publications
(88 reference statements)
1
38
0
8
Order By: Relevance
“…33 Due to its characteristic localization in regions with a high density of apocrine glands, it was initially assumed that the inflammation of these glands, the so called apocrinitis, was the primary event. 34 However, it is now generally accepted that apocrine glands are secondarily involved and the primary histopathologic event seems to be follicular hyperkeratosis with plugging, followed by dilation and rupture of the hair follicle with subsequent inflammation and formation of abscesses and sinus tracts. 34 The cause is likely multifactorial, involving a genetic tendency, smoking, mechanical stress, obesity, immune aberrant response and hormonal abnormalities.…”
Section: Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…33 Due to its characteristic localization in regions with a high density of apocrine glands, it was initially assumed that the inflammation of these glands, the so called apocrinitis, was the primary event. 34 However, it is now generally accepted that apocrine glands are secondarily involved and the primary histopathologic event seems to be follicular hyperkeratosis with plugging, followed by dilation and rupture of the hair follicle with subsequent inflammation and formation of abscesses and sinus tracts. 34 The cause is likely multifactorial, involving a genetic tendency, smoking, mechanical stress, obesity, immune aberrant response and hormonal abnormalities.…”
Section: Pathogenesismentioning
confidence: 99%
“…42 The authors concluded patients with a low and high BMI could represent two clinically different subtypes of HS suggesting a non-linear relationship between BMI and impact of HS. 42 The role of androgens and sexual hormones remains controversial, 34 but many facts support a possible relation: -the typical onset in a narrow age spectrum after puberty; -rare postmenopausal onset 34 ; -usual improvement during pregnancy and post-partum flare-up 34 ; -reports of association with irregular menses, hirsutism and higher concentration of total testosterone, 43 although not constant 28,44 ; -reports of significant remission after antiandrogen therapy, although most of HS patients have normal androgen profiles 45,46 ; -HS in children under 12 is more likely associated with hormonal imbalance, namely adrenal hyperplasia, premature adrenarche, obesity, and metabolic syndrome. 47 In fact, a diagnosis of HS in children may be a marker of precocious puberty.…”
Section: -Obesity and Other Endocrine Abnormalitiesmentioning
confidence: 99%
See 3 more Smart Citations